Production of molybdenum oxide particles with high yield by ultrasonic spray pyrolysis and their catalytic activity toward partial oxidation of n-dodecane - Choi, Hanseul; Kim, Daeho; Yoon, Sung Pil; Han, Jonghee; Ha, Su; Kim, Jinsoo (ELSEVIER SCIENCE BV, 2015)
Molybdenum oxides (MoOx) have shown interesting catalytic and electronic properties for various applications in recent years. However, they are typically synthesized via hydrothermal and solvothermal methods that have a low production yield of less than 1 g per batch. In this study, we developed a large-scale production and continuous process of MoO3 particles by utilizing an ultrasonic spray pyrolysis technology that allows the production rate of MoO3 particles at 4.5 g/h. The size and phase structure of the MoO3 particles were significantly affected by the pyrolysis temperature and concentration of precursor solution used. The as-synthesized MoO3 particles were reduced to MoO2 particles by H-2 treatment at 700 degrees C for 3 h. Partial oxidation reaction was studied to test the catalytic performance of both the MoO3 and MoO2 particles using n-dodecane as a fuel. The MoO3 particles showed 45.3% of H-2 yield and 74.1% of carbon conversion. After reduction, however, the MoO2 particles showed 60.8% of H-2 yield and 87.4% of carbon conversion, which shows higher performance than that of commercial MoO2. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: DIOXIDE-BASED ANODE; HYDROTHERMAL SYNTHESIS; MOO3 NANOBELTS; NANOPARTICLES; TEMPERATURE; PERFORMANCE; NANORODS; ROUTE